Shay Cormac’s Characterization In Assassin’s Creed Rogue Game - Ramadhani, Revanska Ihza; Yuwita, Mia Rahmawati (Mahadaya: Jurnal Bahasa, Sastra, Dan Budaya, 2025)
This research is entitled “Shay Cormac’s Characterization in Assassin’s Creed Rogue Game.” In this study, the authors focus on the classification of the character of Shay Cormac at the beginning and at the end of the storyline. This study employs the theory of the Six Pillars of Human Character, as outlined by Josephson, to derive character classifications such as citizenship, responsibility, respect, caring, and trustworthiness. The research method used in this research uses the descriptive method, which involves collecting data and then observing aspects related to the problem under study. The data obtained is then processed and analyzed further based on the theory that has been studied to obtain a more detailed picture of the object. The findings show that Shay demonstrates responsibility in preventing further destruction, respect in evaluating the actions of different groups, and caring because of his concern for innocent lives, and citizenship to show his integrity. Overall, from this study, we can see that Shay is not a simple character but has many sides. Keywords: Characterization, Six Pillars of Character, Shay Cormac